THE ADVENTURE SPORTS AFTER THE POST MODERNISTIC ERA AND THE MICHEL MAFFESOLI´S IDEAS (Fiep Bulletin - online, 2015)
This article  comes to grips with Michel Maffesoli´s ideas about the post modernistic society and the relation of adventure and risk sports  at this moment, where it seems to  have  had a renascence of an archetypical  structures, archaic ones.There was a preference of outdoors sports, involving the air, like free flying  and free fall. On land, involving mountaineering and tracking. In the water, rafting and also skate street, an adventure sport practiced in urban areas.This study has a qualitative aspect and  its aims are: (a)identify the presence of the characteristics at the post modernity  on the speeches of the practitioners of adventure and hazard  sports in nature and in the urban  environment; (b) verify  the relations existed on the speeches of these practitioners  of these sports that make use of air, land and water.This study  is  characterized  by  a meta analyses , beginning by studies interpretations of Katia Passos (2005)Treking, Manuela Gonsales (2004). Free fall, Fabiana Rodrigues (2004). Rafting, Vera L.Costa (1999), Mountaineering , Maria Regina Costa (2004); Skate Street, Luciana Abdala (2001),  Free flying, and the analyses of the context  beginning by the speeches of these practitioners of hazard and adventure sports. In a initial analysis, we verified that the hazard and outdoors sports match with post modernistic characteristic, conforming qualified in previous studies mentioned. They were times of the tribes, of  nomadism, errant, sensible reason of adventure. The places make the links. It is noticed that  these characteristics emerged from a significant way on the  practitioners of risk and outdoors sports.
Keywords: post modernity; sport; adventure.